Efektivitas Layanan Mediasi dalam Meningkatkan Hubungan Interpersonal Peserta Didik - Gea, Pebriana Resta; Damanik, Hosianna Rodearni; Lase, Famahato; Lase, Justin Foera-era (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the effectiveness of mediation services in improving students’ interpersonal relationships at SMK Swasta Kristen Tomosa 2. Interpersonal conflicts characterized by miscommunication, unhealthy competition, and peer disputes have negatively affected the learning climate, highlighting the need for empirically tested interventions. This research employed a quantitative approach with a pretest–posttest control group design. A total of 30 students were selected through simple random sampling and assigned to experimental and control groups. Data were collected using a Likert-scale questionnaire that met validity and reliability criteria (Cronbach’s alpha > 0.60). Data analysis included normality and homogeneity tests, an independent sample t-test, and N-Gain analysis. The results revealed a significant difference between the experimental and control groups (sig. 2-tailed = 0.000 < 0.05). The experimental group achieved an average N-Gain score of 66% (moderate category), while the control group obtained 17% (low category). These findings indicate that mediation services are effective in enhancing students’ interpersonal relationships, particularly in terms of trust, openness, communication skills, and constructive conflict resolution.